Morphology‐ and Size‐Controlled Fabrication of CdS from Flower‐Like to Spherical Structures and their Application for High‐Performance Photoactivity. Issue 15 (18th February 2019) - Fu, Yimin; Ding, Yuanpeng; Zheng, Lingxia; Zhu, YuFang; Han, Sancan
Abstract : The control on the morphology of semiconductors is one of the most critical issues in modern synthetic chemistry. In this study, we present the shape and size‐controlled conversion of CdS from flower‐like microstructure to spherical nanostructure by simply adjusting the molar ratios of cadmium acetate to thiourea; the morphology transformation was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The mechanism of the influence of using different amounts of thiourea on the shape evolution for CdS was discussed in detail. The photocatalytic degradation experiments for RhB under visible‐light irradiation were performed to investigate the photocatalytic performance of CdS; highly morphology‐ and size‐dependent photoactivity is presented. Taking in consideration the higher photoactivity on monodisperse nano‐spherical CdS, CdS nanosphere film‐based photodetector device has been successfully fabricated by using oil‐water interfacial self‐assembly strategy, using a Ti/Au electrode, which showed the excellent stability and repeatability. The work reveals the mechanism of the morphological transformation of CdS nanoparticles and their photoactivity, which is of great significance in the relevant fields. Abstract : In this work, we present the morphological transformation of CdS from flower‐like to spherical structures, achieved by increasing the amount of thiourea. The mechanism of the shape evolution and the photochemical properties of CdS were also discussed in detail.